Towards a Chronotopical Analysis of Urban Squares - Remm, Tiit (Semiotika, 2024)
This research aims to develop semiotic tools for analysing emergent and recently (re)designed urban everyday spaces, an emergent, changing and internally heterogeneous sociocultural phenomenon. Interlinking environmental semiosis of material space, interpretations by users in (inter)actions and textualisation in culture, the framework of chronotopical analysis is proposed and explored, together with broadening it from literary studies to the domain of urban space. Its application is exemplified in the material of recently (re)designed town squares in Estonia, an outcome of a nationwide program to revitalise small towns and develop the appreciation of public space in Estonian culture. The study outlines the framework of chronotopical analysis and demonstrates its potential for the integrative semiotic analysis of the multi-layered and dynamic character of recently designed urban spaces.
Keywords: urban semiotics; semiotics of space; chronotopical analysis; town squares; Great Public Space